Gendarmerie - the political police of the Russian Empire in the XIX - early XX century: organizational and legal aspects of formation and activity - Ukhach, Vasyl (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
Abstract of the article is caused by the need to ensure public safety, protect the constitutional order, political, economic, scientific, technical and information space Ukraine. In modern Ukrainian historiography there are quite a few monographic works general character dedicated to the establishment and functioning of law enforcement agencies in the Ukrainian lands at different stages of historical development. The aim of the article is to study the organizational and legal basis for the creation, transformation and certain aspects of the gendarmerie - the political policy in the Ukrainian lands as part of the Russian Empire in the XIX - early XX centuries. During the XIX - early XX centuries, law enforcement agencies of the Russian Empire were formed with a clear division of functions and definition of tasks. Securing the state mechanism and the constitutional system of the empire was the main purpose of their operation. The creation of the Gendarmerie Corps, Third Department (The Third Section of His Imperial Majesty`s Own Chancellery) marked the transition tsarist system of political control and police completed the formation mechanism of absolute monarchy. The gendarmerie, as the "supreme police" of the Russian Empire, was given a key role in supporting the autocratic government and fighting crime in all its manifestations, and its sphere of competence was constantly changing depending on the domestic political situation in the country. The corps of gendarmes was created as an elite structural unit in the system of law enforcement agencies of the empire, and therefore the personnel were subject to fairly high requirements. The gradual reorganization of these and other tsarist law enforcement agencies was part of strengthening the state system of the Russian Empire in the difficult conditions of the growing internal crisis and aimed at protecting the foundations of autocracy, fighting crime, suppressing freedom, fighting the revolutionary and national liberation movement.